Antecedents And Consequences Of Cyberloafing Among Knowledge Workers In Malaysian Msc Status Companies: The Moderating Effect Of Duration On Cyberloafing Breaks - Saidin, Siti Salina (2019)
This study examines and validate a reseach model in order to understand the actual cyberloafing behavior among knowledge workers in Malaysian MSC-status companies by adopting the Theory of Interpersonal Behavior (TIB) for the antecedents of cyberloafing (intention to cyberloaf, habit, facilitating condition and ability to hide cyberloafing) and the Consequences of Deviant Usage of Internet Technology (DUIT) in order to investigate the consequences of cyberloafing in terms of work productivity, work stress and online security threats to the organizations. Precisely, this study also investigates whether duration of cyberloafing break moderates the relationship between actual cyberloafing behavior and knowledge workers'work productivity as well as the relationship between actual cyberloafing behavior and knowledge workers' work stress. 264 usable data was obtained through online survey and paper-based survey from knowledge workers in Malaysian MSC-status companies, and twelve hypotheses were tested. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilised to verify the research model in this study. The results show that affect, social factor and perceived consequences were significant belief dimensions of intention to cyberloaf. The intention to cyberloaf, habit and ability to hide cyberloafing were found to be significant antecedent of cyberloafing. However, facilitating conditions was found insignificant as the predictor of cyberloafing. Additionally, work productivity and work stress were found to be significant consequences of cyberloafing. However, online security threat to the organizations was not significant as the consequence of cyberloafing.